Social Support and Academic Stress for Overseas Students : Case Study of Students from Outside Java Island - Michael Agung Nugroho; Christiana Hari Soetjiningsih (Psikostudia : Jurnal Psikologi, 2023)
As overseas students, of course, they have different demands, in addition to carrying out their duties and responsibilities as overseas students, of course, they must be able to adapt to new circumstances and surroundings. Internal and external factors can affect the smoothness and capability of overseas students in getting education at the university level. The responsibilities and demands faced by overseas students are seen to affect education and cause academic stress. The research method used in this study is a quantitative approach, the data analysis technique used in this study is descriptive analysis using descriptive statistics and the participants who acted as subjects in this study amounted to 100 students of Satya Wacana Christian University So, researchers conducted this study with the aim of knowing the correlation between social support and academic stress levels in students who came from outside Java. The results obtained from this study were that there was no correlation between social support and academic stress. The implications of this study highlight the importance of looking at other factors that can affect the academic stress of overseas students and identifying effective strategies to cope with such stress.Sebagai mahasiswa rantau tentu saja memiliki tuntutan yang berbeda, selain melaksanakan tugas dan tanggung jawab sebagai mahasiswa rantau tentunya harus dapat beradaptasi dengan keadaan dan lingkungan sekitarnya yang baru. Faktor internal dan eksternal dapat mempengaruhi kelancaran dan kapabilitas mahasiswa rantau dalam mengenyam pendidikan di tingkat perguruan tinggi. Tanggung jawab dan tuntutan yang dihadapi mahasiswa rantau dipandang dapat mempengaruhi pendidikan dan menyebabkan stres akademik. Metode penelitian yang digunakan dalam penelitian ini yaitu pendekatan kuantitatif, teknik analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif yang menggunakan statistik deskriptif dan partisipan yang berperan sebagai subjek dalam penelitian ini berjumlah 100 mahasiswa Universitas Kristen Satya Wacana Maka, peneliti melakukan studi ini dengan tujuan untuk  mengetahui korelasi antara dukungan sosial dengan tingkat stres akademik pada mahasiswa yang berasal dari luar pulau Jawa. Hasil yang diperoleh dari penelitian ini adalah tidak ada korelasi antara dukungan sosial dengan stres akademik. Implikasi penelitian ini menyoroti pentingnya melihat faktor-faktor lain yang dapat mempengaruhi stres akademik mahasiswa rantau dan mengidentifikasi strategi yang efektif untuk mengatasi stres tersebut.